Cerebrospinal fluid shunt catheter extrusion through the mouth in a child: a case report with brief literature review - Ghritlaharey, Rajendra K. (International Surgery Journal, 2024)
Extrusion of the distal end of the cerebrospinal fluid (CSF) shunt catheter through the mouth is a rare complication of shunt surgery performed to treat hydrocephalus. A two-year-old girl had her first CSF shunt inserted when she was six months old to treat congenital hydrocephalus. The shunt became infected 2-months later and had to be removed. A few weeks later, a new CSF shunt was inserted on the left side. One year later, she presented with an extrusion of the distal end of the CSF shunt catheter through her mouth. However, she showed no symptoms or signs of peritonitis or meningitis. Her entire CSF shunt system on the left side required removal. A cranial magnetic resonance imaging (MRI) scan showed ventriculomegaly and a new CSF shunt catheter was implanted on the right side. She had an uneventful postoperative period and was doing well during the follow-up. Extrusion of the distal end of the CSF shunt catheter through the mouth is rare and more likely to occur in children, and clinicians need to be aware of such complications.